Wild Life in the Tehri-garhwal Himalayas-the Problem of their Conservation - Srivastava, B. P. (Indian Forester, 1969)
The author draws upon his personal observations and experiences during his three years’ tenure in the Tehri-Garhwal Circle to describe the distribution and habits of the varied and often rarely seen wild life in the Himalayan forests of Tehri-Garhwal. The tract with which he deals covers about 3,000 square miles of the Himalayan region varying in altitudes from 500 metres to 5000 metres (1,500 feet to 15,000 feet) above sea-level with flora ranging from the sub-tropical to the alpine or even arctic type. The fauna is equally varied ranging from elephants and tigers in the lower zones to the Himalayan blue sheep, the snow-leopard and the brown bear at the snow-line and the Tibetan wild sheep and the Tibetan black wolf on the higher plateaux. While It is not a report of a methodical faunal survey, it is based on the observations of the author and his experiences during three years of intensive touring in the region. It also describes the dangers, which the interesting wild life of the region is facing from poaching by local villagers and suggests some measures to check the same.